prove geometically that cos(x+y) =cosxcosy-sin xsin y and hence find cos (π/2+x)
Answers
Answer:
cosπ/2cosx-sinπ/2sinx
0-sinx
-sinx
Answer:
What is the proof that cos (x + y) = cos (x) cos (y) − sin (x) sin (y)?
The expansion of cos (α + β) is generally called addition formulae. In the geometrical proof of the addition formulae we are assuming that α, β and (α + β) are positive acute angles. But these formulae are true for any positive or negative values of α and β.
Now we will prove that, cos (α + β) = cos α cos β - sin α sin β; where α and β are positive acute angles and α + β < 90°.
Let a rotating line OX rotate about O in the anti-clockwise direction. From starting position to its initial position OX makes out an acute ∠XOY = α.
Again, the rotating line rotates further in the same direction and starting from the position OY makes out an acute ∠YOZ = β.
Thus, ∠XOZ = α + β < 90°.
We are suppose to prove that, cos (α + β) = cos α cos β - sin α sin β.
Construction: On the bounding line of the compound angle (α + β) take a point A on OZ, and draw AB and AC perpendiculars to OX and OY respectively. Again, from C draw perpendiculars CD and CE upon OX and AB respectively.
Proof: From triangle ACE we get, ∠EAC = 90° - ∠ACE = ∠ECO = alternate ∠COX = α.
Now, from the right-angled triangle AOB we get,
cos (α + β) = OB/OA
= OD−BD/OA
= OD/OA - BD/OA
= OD/OA - EC/OA
= ( OD/OC ∙ OC/OA) - ( EC/AC ∙ AC/OA)
= cos α cos β - sin ∠EAC sin β
= cos α cos β - sin α sin β, (since we know, ∠EAC = α)
Therefore, cos (α + β) = cos α cos β - sin α sin β. Proved
Well, there is another good proof given in NCERT..(which may be a bit simpler)..So, you may refer to that for more transparency of the proof..
Hope this was helpful
Regards.
Step-by-step explanation: